2021
DOI: 10.3390/ijerph18031339
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of an Educational Intervention to Improve Water Intake in Adolescent Soccer Players: A Two-Arm, Non-Randomized Controlled Cluster Trial

Abstract: This study aimed to assess the feasibility of an educational intervention on hydration behavior in adolescent soccer players. A pilot study of a two-arm, non-randomized controlled cluster trial was conducted. A total of 316 players aged 13–16 agreed to participate. The response variables were the players’ participation in the intervention, their perception of the knowledge acquired, the usefulness and the overall assessment of the intervention. Hydration patterns and acquisition of knowledge on hydration behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Effective interventions include talks, informative posters, infographics, and web or mobile applications. These interventions have been shown to improve knowledge and habits in young soccer players [ 42 , 43 , 44 ]. In our study, we found that U19-17 soccer players had lower values for SR, fluid intake, and weight loss after exercise compared to U23-21 soccer players, particularly during summer training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective interventions include talks, informative posters, infographics, and web or mobile applications. These interventions have been shown to improve knowledge and habits in young soccer players [ 42 , 43 , 44 ]. In our study, we found that U19-17 soccer players had lower values for SR, fluid intake, and weight loss after exercise compared to U23-21 soccer players, particularly during summer training.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological differences may contribute to discrepancies in these values. Factors such as a higher basal metabolic rate in adults, a higher body mass to body surface area ratio, more efficient thermoregulatory capacity in adults, physiological development, and established hydration habits may result in a greater need for thermoregulation through sweating during exercise [ 4 , 42 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atkins WC et al [ 48 ] have reported that educational intervention improves hydration status and behaviours in high school football players. Martín-Payo [ 49 ] has also reported that feasible educational intervention improves hydration behaviour in adolescent soccer players, but hydration guidelines should be based on personal factors. In a word, an appropriate and personalized rehydration education is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated a lower rate of hypohydration in football players [ 13 , 15 ]. It is well established that thirst does not constitute a proper measure for dictating fluid intake, and proper hydration guidance should be provided to players to prevent hypohydration and induce proper hydration levels [ 15 , 25 ]. The results of this study support this suggestion, since the educational intervention that was implemented in order to advise for proper hydration resulted in progressively lower dehydration rates in players participating in this series of football fixtures.…”
Section: Discussionmentioning
confidence: 99%